Teachers’ Self-Efficacy and Teacher-Initiated Parental Involvement: The Two-Tier Lens on Teachers’ Performance - Maldia, Sheryl Manarin (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study examined the relationship between teachers’ self-efficacy, teacher-initiated parental involvement, and their impact on the performance of elementary teachers in DepEd SDO Sto. Tomas City. A total of 261 public elementary school teachers participated, using a descriptive correlational design to assess the variables through a survey questionnaire. Results showed that teachers rated their self-efficacy as "Very High" and their parental involvement as “High,” demonstrating excellent overall performance. The findings revealed moderate to strong positive correlations between both self-efficacy and parental involvement with teachers’ performance. Key predictors of performance included cooperation with colleagues, overall self-efficacy, and community collaboration, with self-efficacy, learning at home, and community engagement positively correlating with performance, while collaboration with colleagues was negatively correlated. In conclusion, higher levels of teachers’ self-efficacy and active parental involvement are essential for sustaining high teaching performance